The master’s degree in development practice: a case study of twelve university programs - Clarke, Faith; Gano, Gretchen; Currey, Robin; Alleyne, John (Frontiers in Sustainability, 2024)
Sustainable development is a global priority. However, a lack of research exists on the programs designed to train sustainable development practitioners. This multi-case case study, possibly the first to describe the programs that trains development practitioners, utilized case study theory and semi-structured interviews with program administrators to describe sustainable development programs offered by 12 higher education institutions in eight countries with membership in the Global Association of Masters in Development Practice. The results revealed five themes or key drivers, nine advantages, and four deficiencies. Two drivers were enrollment-focused (admission of students with prior work experience in development and financial support), two were curriculum-focused (incorporation of field work and integration of specific knowledge aspects and skills training in the curricula), and one was institutional attitude (adoption of a culture of flexibility). The most common challenges were impacts from the COVID-19 pandemic. These results provide insights for continuous improvement efforts of program administrators for students in sustainable development. The practical methodology developed can be replicated and adapted for investigation of similar programs and other disciplines in higher education.